2021
DOI: 10.15252/embr.202052079
|View full text |Cite
|
Sign up to set email alerts
|

Quaking 5 suppresses TGF‐β‐induced EMT and cell invasion in lung adenocarcinoma

Abstract: Quaking (QKI) proteins belong to the signal transduction and activation of RNA (STAR) family of RNA-binding proteins that have multiple functions in RNA biology. Here, we show that QKI-5 is dramatically decreased in metastatic lung adenocarcinoma (LUAD). QKI-5 overexpression inhibits TGF-b-induced epithelialmesenchymal transition (EMT) and invasion, whereas QKI-5 knockdown has the opposite effect. QKI-5 overexpression and silencing suppresses and promotes TGF-b-stimulated metastasis in vivo, respectively. QKI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…This point was further strengthened by the evidence that ALKBH5 dramatically inhibited TGF-βinduced upregulation of p-SMAD3 (Supporting Information Figure S3), a hallmark of TGF-β/SMAD activation. 36,37 Combining with our previous findings that TGF-β/SMAD signaling activation promotes TGF-βinduced EMT in NSCLC cells, 8,9 the present data suggest that ALKBH5 suppresses TGF-βinduced EMT by erasing m 6 A modification of TGF-β/SMAD signaling components and inhibitory regulator, including TGFβR2/SMAD3 and SMAD6. Of course, we can′t exclude ALKBH5-mediated m 6 A demethylation of other signaling pathways affecting TGF-βinduced EMT (Figure 4D).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This point was further strengthened by the evidence that ALKBH5 dramatically inhibited TGF-βinduced upregulation of p-SMAD3 (Supporting Information Figure S3), a hallmark of TGF-β/SMAD activation. 36,37 Combining with our previous findings that TGF-β/SMAD signaling activation promotes TGF-βinduced EMT in NSCLC cells, 8,9 the present data suggest that ALKBH5 suppresses TGF-βinduced EMT by erasing m 6 A modification of TGF-β/SMAD signaling components and inhibitory regulator, including TGFβR2/SMAD3 and SMAD6. Of course, we can′t exclude ALKBH5-mediated m 6 A demethylation of other signaling pathways affecting TGF-βinduced EMT (Figure 4D).…”
Section: Discussionsupporting
confidence: 83%
“…Considering that TGF‐β signaling‐mediated EMT is involved in NSCLC metastasis, 8,9 we performed gene set enrichment analysis (GSEA) based on http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc%3DGSE19804 from GEO database to predict whether ALKBH5 may regulate TGF‐β signaling‐mediated EMT. Notably, GSEA showed that three gene sets, including epithelial cell migration, EMT and TGF‐β signaling pathway, were dramatically enriched in NSCLC patients with low ALKBH5 expression (Figure 1D–F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TSPAN1 promoted EMT and metastasis of cholangiocarcinoma by activating PI3K/AKT pathway, and we also revealed a similar mechanism in breast cancer [ 18 ]. EMT causes tumor epithelial cells to lose their polarity, converts adherent phenotypes into mesenchymal forms, and increases the ability of cancer cells to invade and migrate [ 28 ]. EMT also plays a key role in the metastasis of malignant tumor cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EMT that is associated with TGF-β/Smads signaling can be suppressed by lncRNA Smad3-associated long non-coding RNA (SMASR), which are close to Smad3 in lung cancer cells [ 93 ]. Similarly, in lung cancer cells, TGF-β induced EMT could also be suppressed by quaking 5 (QKI-5) protein via binding directly to the 3′UTR region of TGFR1 to degrade its mRNA [ 94 ].…”
Section: Tgf-β Signaling In Carcinoma Plasticitymentioning
confidence: 99%